The man who stayed behind - Rittenberg, Sidney 1921-2019; Bennett, Amanda (Simon & Schuster, 1993)
The story of "an idealistic young American who freely cast his lot with the Chinese revolution only to be struck down by that revolution at the floodtide of its success."--Leonard Woodcock, first American Ambassador to China.
Keywords: Rittenberg, Sidney; Rittenberg, Sidney -- 1921-2019; Geschichte 1949-1976; Geschichte; Communists -- China -- History -- Biography; Autobiografie; USA; China -- History -- 1949-1976; China -- History -- Civil War, 1945-1949; United States -- Biography; China; Biografie